Modelagem biométrica de árvores com crescimento livre e sob competição em floresta de araucária - Costa, Emanuel Arnoni (2015)
This study was developed with aim of applying the modeling biometric of open-grown trees and under competition in Araucaria Forest. Data were collected in three cities in southern Brazil: Canoinhas (SC), Lages (SC) and São Francisco de Paula (RS). In eleven chapters were introduced studies for evaluating the growth space, the dimensional characteristics of trees, attributes of crown size, the influence of competition between trees, the radial increment modeling at the level of diameter at breast height, the crown efficiency, develop density management dendrograms in Araucaria Forest and propose strategies for regulation of araucaria wood yield in natural forest. The results of this study allows us to improve forest decisions to be executed for araucaria in area of natural occurrence.